2002
DOI: 10.1364/ol.27.000812
|View full text |Cite
|
Sign up to set email alerts
|

Photonic crystal fiber coupler

Abstract: Fiber couplers made with photonic crystal fibers (PCF) are reported. Two types of PCF were fabricated by means of stacking a group of silica tubes around a silica rod and drawing them. The fiber couplers were made by use of the fused biconical tapered method. With a fiber that had five hexagonally stacked layers of air holes, a 33/67 coupling ratio was obtained, and with a one-layer four-hole fiber, a 48/52 coupling ratio was obtained. The fabrication processes and the characteristics of the PCFs and the PCF c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(41 citation statements)
references
References 4 publications
0
39
0
2
Order By: Relevance
“…The first PCF coupler was fabricated by the FBT method in 2002 with home-made PCFs [10]. With the PCF having only one layer of 4 large holes and having 5 layers of many small holes, the PCF couplers could be fabricated.…”
Section: Photonic Crystal Fiber Couplermentioning
confidence: 99%
See 2 more Smart Citations
“…The first PCF coupler was fabricated by the FBT method in 2002 with home-made PCFs [10]. With the PCF having only one layer of 4 large holes and having 5 layers of many small holes, the PCF couplers could be fabricated.…”
Section: Photonic Crystal Fiber Couplermentioning
confidence: 99%
“…Recently, the HAF coupler has been successfully fabricated by using the FBT method and with a ceramic heater, which had better control in the heating temperature over the conventional hydrogen flame heater [18]. In order to prevent air hole collapsing of the HAF during the fusion process, the ceramic heater temperature was intentionally lowered by a couple of hundred degrees below the one for the conventional SMF coupler [10]. In experiment, it was observed that the coupling action commenced at an elongation length of about 9 mm, which was a little bit longer than the SMF case of 7 mm [11].…”
Section: Fiber Coupler Based On Hole-assisted Fiber With a Ge-dopmentioning
confidence: 99%
See 1 more Smart Citation
“…The DCF coupler was realized simply by allowing physical contact between the inner cladding regions of two pieces of DCFs. This process did not require additional fabrication equipment or complex fabrication processes generally used for the conventional fabrication methods such as the side polishing method [11] and the fused bi-conical tapered (FBT) method [12]. To secure the contact, a pair of DCFs was twisted around each other after removing the polymer jackets (the outer cladding) as shown in Fig.…”
Section: Double Clad Fiber Couplermentioning
confidence: 99%
“…It is worthy to note that besides the one-core PCF, multi-core PCFs including dual-core PCFs (DC-PCFs) have also been proposed for special applications. DC-PCFs have been designed for coupling inside PCFs [57][58][59][60], which can be used to achieve compact PCF couplers. Koshiba's group has proposed a wavelength MUX-DEMUX based on a DC-PCF [61], a polarization splitter based on a three-core PCF [62], a narrow band-pass filter [63] and a 1 × 4 power splitter [64] based on multi-core PCFs.…”
Section: Introductionmentioning
confidence: 99%